Dissolution Effect of Alteplase on Arterial Blood Clot Model of Hypertensive Intracerebral Hemorrhage Patients in vitro - Jiang, Xiaoming; Lu, Yongyu; Hu, Xiaogang; She, Xiaochun (Frontiers in Neurology, 2022)
Objective To explore the dissolution effect of alteplase (rt-PA) on arterial blood clots of patients with hypertensive cerebral hemorrhage in vitro and analyze the optimal concentration and action time of rt-PA for intracranial hematomas. Methods The arterial blood of 35 patients with confirmed hypertensive cerebral hemorrhage were collected, centrifuged, and the serum was aspirated to prepare the blood clot model. The 0.125, 0.25, 0.5, 1, 2, and 3 mg t-PA, 20,000 U, and 40,000 U urokinase (u-PA) were taken for the corresponding blood clot for dissolution test. The blood clot volume and dissolution volume was measured at 0, 30, 60, 90, 120, and 150 min. Results Without intervention, the blood clot volume of men was higher than that of women at 0, 30, 60, and 90 min (P < 0.05). Without intervention, hematocrit (HCT) was correlated with blood clot volume and the correlation decreased with time. The 30, 60, and 90 min dissolution curves of each group showed an upward trend (P < 0.05), and the dissolution curves tended to be flat at 120 min and 150 min. The dissolution volume of.125 mg/3 ml, 0.25 mg/3 ml, 0.5 mg/3 ml rt-PA, 20,000 U, 40,000 U u-PA was higher than that of 1, 2, 3 mg/ml rt-PA (P < 0.05). The dissolution volume of.125 mg/3 ml, 0.25 mg/3 ml, 0.5 mg/3 ml rt-PA was not significantly different from 20,000 and 40,000 U u-PA (P > 0.05). Gender differences did not affect the effects of the above drugs. Conclusion In vitro, low-concentration rt-PA has a better dissolution effect, and it shows a time-dependent effect, reaching the highest effect in 90 min.